Knock-Down of a Tonoplast Localized Low-Affinity Nitrate Transporter OsNPF7.2 Affects Rice Growth under High Nitrate Supply - Hu, Rui; Qiu, Diyang; Chen, Yi; Miller, Anthony J.; Fan, Xiaorong; Pan, Xiaoping; Zhang, Mingyong (Frontiers in Plant Science, 2016)
The large nitrate transporter 1/peptide transporter family (NPF) has been shown to transport diverse substrates, including nitrate, amino acids, peptides, phytohormones, and glucosinolates. However, the rice (Oryza sativa) root-specific family member OsNPF7.2 has not been functionally characterized. Here, our data show that OsNPF7.2 is a tonoplast localized low-affinity nitrate transporter, that affects rice growth under high nitrate supply. Expression analysis showed that OsNPF7.2 was mainly expressed in the elongation and maturation zones of roots, especially in the root sclerenchyma, cortex and stele. It was also induced by high concentrations of nitrate. Subcellular localization analysis showed that OsNPF7.2 was localized on the tonoplast of large and small vacuoles. Heterologous expression in Xenopus laevis oocytes suggested that OsNPF7.2 was a low-affinity nitrate transporter. Knock-down of OsNPF7.2 retarded rice growth under high concentrations of nitrate. Therefore, we deduce that OsNPF7.2 plays a role in intracellular allocation of nitrate in roots, and thus influences rice growth under high nitrate supply.